Helical sense selective domains and enantiomeric superhelices generated by Langmuir–Schaefer deposition of an axially racemic chiral helical polymer. Issue 6 (21st January 2016) - Rodríguez, R.; Ignés-Mullol, J.; Sagués, F.; Quiñoá, E.; Riguera, R.; Freire, F.
Abstract : An axially racemic chiral helical polymer generates left- and right-handed monolayers and enantiomeric superhelices by LS deposition. Abstract : The chiral polymer poly-( R )-1 behaves in solution, despite its chiral pendants, as a dynamic axially racemic ( i.e., 1 : 1) mixture of left- and right-handed helices, but its deposition on graphite by a Langmuir–Schaefer (LS) technique leads to a helical sense-selective packing that forms separate enantiomeric domains of left- and right-handed helical chains observed by high resolution atomic force microscopy (AFM). The polymer structure within these domains is very uniform, seldom altered by the presence of reversals, grouped always in contiguous pairs maintaining a single helical sense along the polymer chain. The LS deposition technique has been shown to be crucial to obtain good quality monolayers from poly-( R )-1 and other poly(phenylacetylene)s (PPAs: poly-2, poly-3 and poly-4) with short pendants, where spin coating, drop casting and Langmuir–Blodgett (LB) failed, and suggests that this technique could be the method of choice for the preparation of 2D monolayers for high resolution AFM studies of PPAs with short pendants. Key helical parameters ( i.e., sense, pitch, packing angle) are easily measured in this way.